Short Report: Exploring the extent to which Intellectual Disability is undiagnosed within children attending developmental paediatric clinics. (December 2022) - Delahunty, Lauren; O'Hare, Anne; Marryat, Louise; Stewart, Tracy M.; McKenzie, Karen; Murray, George; Kaza, Nandita
Abstract: Intellectual Disability is under-ascertained worldwide and is associated with greater physical and mental health difficulties. This research aimed to identify clinical features and characteristics of children with Intellectual Disability in a population of 126 6–18 year olds in mainstream school, attending paediatric developmental clinics. Intellectual Disability was defined according to the DSM-5 (deficits in intellectual and adaptive functioning, present during childhood). Measures used to assess this were WISC-IV IQ (score <70) and ABAS adaptive behaviour (score =<70). Clinical features were compared from a structured clinical records investigation and logistic regression explored which factors were associated with Intellectual Disability. Twenty-eight children (22%) met the criteria for Intellectual Disability. Five variables were associated with higher odds of having Intellectual Disability: no other neurodevelopmental diagnosis, multiple other health problems, prior genetic testing, maternal smoking during pregnancy, and parental unemployment. Routinely-collected paediatric data only predicted Intellectual Disability correctly in two out of five cases. Further research is needed to verify these findings and improve identification. What this paper adds?: Many children with Intellectual Disability, particularly a milder version, still reach adulthood without a diagnosis, despite evidence indicating that diagnosis is generally well received by children and families, and that early intervention leads to improvements in outcomes. This short report, based on a small sample of 126 children aged 6–18 in mainstream school who attended a paediatric development clinic in South East Scotland, provides tentative data on the clinical features and characteristics which are associated with Intellectual Disability. This tentative evidence suggests that the combination of a) having multiple concerns and investigations, alongside b) one or both parents being out of work (which may be related to familial undiagnosed Intellectual Disability), should raise a flag for paediatricians to further investigate the possibility of an Intellectual Disability diagnosis among these children and young people. Further research with larger samples is needed to explore this more robustly, with the potential to create an algorithm to highlight to paediatricians cases requiring formal screening for Intellectual Disability.